LER/DORT e fibromialgia : dificuldades diagnósticas. Avaliação dos sintomas músculoesqueléticos em eletricistas - Alencar, Jeronimo Farias de (Universidade Federal de São Carlos, 2008)
This thesis presents papers developed during the Ph.D studies, expressed by an article accept for publication (Study I), and a second one submitted (Study II). Also preliminaries results are shown in a third study (Study III). In the beginning of the introduction of this thesis a contextualization of difficulties on the diagnosis of Repetitive Strain Injuries (RSI)/ Work Related Musculoskeletal Disorders (WMSD) and fibromyalgia is presented. These difficulties have justified the development of a study denominated Relevant Aspects on WMSD and Fibromyalgia diagnosis "(Study I). In this study 75 physicians, (36 assistants and 39 experts), answered structured and open questions about aspects that they consider relevant to the establishment of diagnosis of these two syndromes. The analysis of the results showed that general physicians tended to emphasize the factor clinical conditions and time elapsed , while occupational physicians tended to indicate occupational history as main factor for diagnosis of the WMSD. The results suggested, among other aspects, the necessity to take into account the risks at work as a differential aspect between RSI/WMSD and fibromialgia. Following our initial plan of work, we accomplished a new study that included evaluation of musculoskeletal symptoms and occupational risks. The chosen population was linemen who worked at an energy distribution company, as the risks present in their work have not been described in the literature. The study was entitled "Musculoskeletal symptoms in energy distribution linemen (Study II). 30 linemen from three different working sectors participated in this study. The results showed high number of musculoskeletal symptoms that varied according to the linemen' activities. Regarding the body areas affected, the shoulders presented higher discomfort rate. These results have motivated the development of the third study entitled Preliminary results of postural risks in power line electricians using inclinometry (Study III). In this study quantitative measurements of shoulder movements were carried out during five more frequent occupational activities, chosen by the analysis of a company routine recording of the occupational activities performed by the workers. Due to safety regulations, it was not possible to perform direct measurements of the workers while the power lines were energized. Thus, the recordings were performed at a technological center in which the occupational environment is reproduced for the workers training. In these centers the environment and activities are similar to the real ones but the lines are not energized to prevent electrical shock. 12 power workers from maintenance and emergency sectors (low tension) took part in the study. The preliminary results showed that the 5 analyzed activities presented postural risks for the development of musculoskeletal symptoms related at work. These studies gave us the possibility to investigate the clinical aspects for the establishing of the diagnosis of RSI/WMSD and fibromyalgia, to evaluate symptoms in workers at risk during occupational activities performed by electricians, as well as to quantify the level of postural overload related to WRMS occurrence in power men through direct measurements.
Keywords: LER/DORT (Lesões por Esforços Repetitivos/Disturbuios Osteomusculares Relacionados ao Trabalho); Fibromialgia; Inclinômetria; Fatores de risco; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL